Application of an improved problem-based learning method in clinical endodontic training of standardized residents - Wen Jiang; Jun Yang; Qi Yu; Yadong Chen; Yan Tu (BMC Medical Education, 2026)
Abstract Standardized residency training in stomatology is essential for developing competent dental professionals; however, improving clinical skills effectively remains a challenge in dental education. In this study, we implemented an improved problem-based learning (PBL) approach in endodontic clinical practice and evaluated its effects on residents’ clinical performance as well as residents’ and teachers’ perceptions of this teaching method. A total of 120 residents undergoing standardized residency training in endodontics between January 2023 and December 2025 were randomly assigned to either an experimental group (improved PBL, n = 60) or a control group (conventional PBL, n = 60). Clinical competency was independently assessed for Root Canal Treatment (RCT) and Rubber Dam Isolation (RDI) using the Directly Observed Procedural Skills (DOPS) assessment at baseline (course start) and upon completion of the course, and feedback questionnaires were used to evaluate residents’ and teachers’ perceptions of the teaching approaches. Both groups showed significant within-group improvements across most DOPS dimensions for both procedures. Between-group analyses revealed that for RCT, the improved PBL group showed significant advantages in specific domains including operational capability and obtaining patient consent. Conversely, for RDI, advantages of the improved PBL model were primarily observed in interpersonal domains such as communication skills and humanistic care, with no significant difference in operational capability. Questionnaire findings suggested generally positive perceptions of the improved PBL method among both residents and teachers, particularly with respect to theoretical understanding, clinical teaching, and autonomous learning. Overall, the improved PBL approach demonstrated targeted advantages in fostering specific clinical competencies, highlighting distinct pedagogical benefits depending on the complexity and technical demands of the specific clinical procedure. Further multicenter studies with larger sample sizes are needed to confirm its effectiveness and generalizability.